Radiative MHD Non-Newtonian Chemically Reactive Nanofluid Flow with Heat Source Induced by Non-linear Stretching Cylinder - Makkar, Vinita; Poply, Vikas; Sharma, Naresh (Trends in Sciences, 2022)
Magnetohydrodynamic (MHD) chemically reacting flow by Casson nanofluid bounded by a stretched surface is analyzed. Convective conditions of transport phenomena, radiation and heat generation /absorption effects are discussed. Influence of Brownian motion and thermophoresis has been taken into account. This manuscript investigates the outcomes of yield stress, thermophoresis, Brownian motion, magnetic parameter, Prandtl number, radiation parameter and thermal conductivity on velocity, temperature and nanoparticle concentration profiles. To solve transformed equations, a well designed numerical technique (Runge Kutta Fehlberg) has been implemented by following Shooting procedure. MATLAB programming with ODE45 solver is used to calculate results and compare for local Nusselt number (-qa¢(0)) with extant outcomes in the absence of nanofluid parameters via table and bar graphs for pertinent values of Prandtl number and non linear stretching parameter. An excellent agreement is noted for linear and non-linear stretching cylinder. The impact of controlling fluid parameters is represented graphically. Additionally, physical quantities of interest are tabulated and explained via graphs. GRAPHICAL ABSTRACT